Strategi Pemasaran Digital Lembaga Filantropi Islam - Ulfa Junidar (Tadabbur: Jurnal Peradaban Islam, 2020)
Strategy digital marketing is a step taken by the Islamic philanthropic institution in introducing all products or social programs by disseminating information, approaching/offering to potential donors to be willing to help materially and morally by using online digital media in a certain period of time. Islamic philanthropy is the act of a Muslim who loves his fellow human beings and the value of humanity, thus contributing his time, money, and energy to help others with Islamic values. The purpose of this study is to examine the marketing strategies used by PKPU and Rumah Zakat through digital media in disseminating each program of the institution and to analyze strategy digital marketing to the collection and distribution of ZIS funds by PKPU and Rumah Zakat from 2012-2017. This research is qualitative research with a descriptive analysis method that focuses on the primary data source and secondary data. Methods of data collection are observation, interviews, and online media surveys. The results show that strategy digital marketing used by PKPU and Rumah Zakat with an Integrated digital marketing method consisting of content marketing, mobile marketing, continuous marketing, visual marketing, personalized marketing. Strategy digital marketing is giving a positive influence on the collection and distribution of people's funds by PKPU and Rumah Zakat. It is suggested that to develop institutional capacity in providing human resources of Islamic philanthropy is expected to keep increasing the creative and innovative IT capability in marketing the program and also make it easier for potential donors and donors to access the offered programs.